Interaction of herpes simplex virus RNase with VP16 and VP22 is required for the accumulation of the protein but not for accumulation of mRNA - Taddeo, Brunella (National Academy of Sciences, 2007)
The virion host shutoff (vhs) protein encoded by the U(L)41 gene of herpes simplex virus 1 is an endoribonuclease. The enzyme is introduced into the cell during unpackaging of the virion upon entry and selectively degrades mRNA for several hours. The RNase activity ceases after the onset of synthesis of late (γ) viral proteins. Here we report that vhs protein does not accumulate in cells transiently transfected with only a plasmid encoding the U(L)41 gene. However, vhs does accumulate in cells cotransfected with plasmids expressing two other tegument proteins, VP16 and VP22. vhs does not directly interact with VP22 but, instead, binds VP22 only in the presence of VP16. In contrast to these findings, the amounts of vhs mRNA accumulating in the cells transfected solely with vhs are not significantly different from those detected in cells coexpressing vhs, VP16, and VP22. We conclude from these studies that the steady state of vhs mRNA, reflecting synthesis and turnover of mRNA, is not affected by the interaction of vhs protein with VP16 with VP22. A model is proposed in which the vhs protein may function to sequester mRNAs in compartments inaccessible to the cellular translational machinery and that VP16 and VP22 rescue the mRNAs by interacting with the vhs protein.